Introduction to cardiopulmonary exercise testing - Luks, Andrew M. (Springer New York, 2013)
Cardiopulmonary exercise testing is an important diagnostic test in pulmonary medicine and cardiology. Capable of providing significantly more information about an individual's exercise capacity than standard exercise treadmill or 6-minute walk tests, the test is used for a variety of purposes including evaluating patients with unexplained exercise limitation or dyspnea on exertion, monitoring disease progression or response to treatment, determining fitness to undergo various surgical procedures and monitoring the effects of training in highly fit athletes. Introduction to Cardiopulmonary Exercise Testing is a unique new text that is ideal for trainees. It is presented in a clear, concise and easy-to-follow manner and is capable of being read in a much shorter time than the available texts on this topic. Chapters describe the basic physiologic responses observed during sustained exercise and explain how to perform and interpret these studies. The utility of the resource is further enhanced by several sections of actual patient cases, which provide opportunities to begin developing test interpretation skills. Given the widespread use of cardiopulmonary exercise testing in clinical practice, trainees in pulmonary and critical care medicine, cardiology, sports medicine, exercise physiology, and occasionally internal medicine, will find Introduction to Cardiopulmonary Exercise Testing to be an essential and one of a kind reference.